Posterior reversible encephalopathy syndrome (PRES) after bevacizumab therapy for metastatic colorectal cancer - Mohsin Hamid; Ali Ghani; Ida Micaily; Usman Sarwar; Bilal Lashari; Faizan Malik (Greater Baltimore Medical Center, 2018)
Posterior reversible encephalopathy syndrome (PRES) is an increasingly recognizable neuro-clinical syndrome. Clinical and neurological manifestations of PRES include hypertension, headache, encephalopathy, seizures, and symmetrical white matter changes on brain MRI. Most common precipitants of PRES are acute medical illness, hypertensive crisis, eclampsia, immunosuppressive therapy, and chemotherapy. Bevacizumab is a monoclonal antibody that halts angiogenesis by inhibiting vascular endothelial growth factor. It has gained widespread popularity in oncology world especially for metastatic and recurrent cancers due to its inherent ability to stop angiogenesis; a vital step for tumor growth. Bevacizumab has also been implicated as the cause of PRES due to dysregulation of the blood-brain barrier. We are reporting a case of PRES induced by Bevacizumab in a patient of colorectal cancer.